Comparison of sulfate radical with other reactive species. (December 2022) - Duan, Xiaodi; Niu, Xiaoxiao; Gao, Jiong; Wacławek, Stanisław; Tang, Liang; Dionysiou, Dionysios D
Abstract : Sulfate radical-based advanced oxidation processes have been a research hotspot for decades because of their high efficiency in removing refractory organic contaminants, whereas the development of theoretical and analytical technologies brings the related studies into a new stage in recent years. This opinion compares sulfate radical (SO4 - ) with other reactive species (hydroxyl radical, carbonate radical anion, reactive chlorine species, reactive nitrogen species, and nonradical species) regarding reactivity toward diverse organic compounds, oxidation mechanisms, generated transformation products, and their toxic effects. Experimental and computational tools, such as competition studies by probe compounds, density functional theory, and machine learning, could assist in distinguishing the role of SO4 - with other reactive species. Graphical Abstract: ga1 Highlights: The comparison of sulfate radical with other reactive species is presented. Probe methods, DFT, and machine learning are powerful tools to study SR-AOPs. The future focus can be on exploring SR-AOPs with modern techniques.